Resveratrol-nitric oxide donor hybrid effect on priapism in sickle cell and nitric oxide-deficient mouse - Pinheiro, Andressa Kely; Pereira, Dalila Andrade; Santos, Jean Leandro dos [UNESP]; Calmasini, Fabiano Beraldi; Alexandre, Eduardo Costa; Reis, Leonardo Oliveira; Burnett, Arthur L.; Costa, Fernando Ferreira; Silva, Fábio Henrique (Public Library of Science (PLoS), 2022)
Background Children and adult with sickle cell disease (SCD) display priapism associated with low nitric oxide (NO) bioavailability and oxidative stress in penis. Aim This study aimed to evaluate the effects of hybrid compound RVT-FxMe, derived from resveratrol bearing a NO-donor subunit, on two murine model that display priapism phenotype, SCD transgenic mice and endothelial NO synthase gene-deficient (eNOS-/-) mice. Methods Wild-type, SCD, and eNOS-/- mice were treated with RVT-FxMe (25 mg/kg/d, 2 weeks). Outcomes Hematological parameters, concentration-response curves to acetylcholine (ACh) and sodium nitroprusside (SNP), as well as to electrical field stimulation (EFS), were obtained in mice corpus cavernosum strips. Results Corpus cavernosum relaxations to SNP and EFS were increased in eNOS-/- group, which were normalized by RVT-FxMe treatment. SCD mice exhibited an excessive CC relaxant response induced by ACh, EFS and SNP RVT-FxMe treatment did not change the increased relaxant responses to ACh, EFS and SNP in corpus cavernosum from SCD group. Clinical translation Excess of plasma hemoglobin in SCD may interfere in pharmacological activity of NO donors compounds. Strength/Limitations While mechanistic data with promising potential is showed, the current study is not without limitations. RVT-FxMe effects in the mid- and long-term warrant complementary studies. Conclusion Treatment with RVT-FxMe reversed the enhanced NO-cGMP-mediated CC relaxations in eNOS-/- mice, but not in SCD mice; it is likely that excess of plasma hemoglobin in SCD mice act to inactivate NO before it reaches soluble guanylyl cyclase, avoiding restoration of NO bioavailability in penis.